Clinical and Aetiological Pattern of Chronic Diarrhoea in a Tertiary Care Hospital - Islam, MN; Amiruzzaman, -; Azhar, MA; Yeasmin, S; Hasan, N; Chakraborty, A; Masum, AA (TAJ: Journal of Teachers Association, 2018)
Chronic diarrhoea is one of the most common conditions facing both primary care clinicians and gastroenterologistsThe present study was a cross-sectional study conducted on 100 patients at the Department Medicine and Gastroenterology of Sir Salimullah Medical College, Mitford Hospital, Dhaka. Patients with chronic diarrhoea of at least 4 weeks duration were enrolled in the study. Data were collected using a structured questionnaire. The mean age was 39.14± 14.74 years with a range of 18 to 70 years. The male to female ratio was roughly of 2:1. Among the female 24% were housewives. Equal percentages of patients had abdominal pain, anorexia & significant weight loss (64%). Other clinical features were anemia (34%) fever and rectal bleeding (24%). The leading diagnoses were irritable bowel syndrome (34%), ulcerative colitis (18%), intestinal tuberculosis (12%), chronic pancreatitis (6%), carcinoma colon, intestinal lymphoma, non specific colitis &Crohn’s disease (4% each). Endoscopy of upper GIT was done in 14% patients, colonoscopy 66%, double balloon enteroscopy 6% and specific histological diagnosis found in 56%, 10% was non-specific, 6% was diagnosed by ultrasound and 1% by stool routine examination. It was found that IBS, inflammatory bowel disease and intestinal tuberculosis are the leading cause in our country. Aetiology of chronic diarrhoea can be diagnosed by good history, clinical examinations and an appropriate investigation of which colonoscopy is most useful. TAJ 2016; 29(1): 43-48